Differential Patterns of Inputs Create Functional Zones in Central Nucleus of Inferior Colliculus - Loftus, William C. (Society for Neuroscience, 2010)
Distinct pathways carry monaural and binaural information from the lower auditory brainstem to the central nucleus of the inferior colliculus (ICC). Previous anatomical and physiological studies suggest that differential ascending inputs to regions of the ICC create functionally distinct zones. Here, we provide direct evidence of this relationship by combining recordings of single unit responses to sound in the ICC with focal, iontophoretic injections of the retrograde tracer Fluoro-Gold at the physiologically characterized sites. Three main patterns of anatomical inputs were observed. One pattern was identified by inputs from the cochlear nucleus and ventral nucleus of the lateral lemniscus in isolation, and these injection sites were correlated with monaural responses. The second pattern had inputs only from the ipsilateral medial and lateral superior olive, and these sites were correlated with interaural time difference (ITD)-sensitive responses to low frequency (<500 Hz). A third pattern had inputs from a variety of olivary and lemniscal sources, notably the contralateral lateral superior olive and dorsal nucleus of the lateral lemniscus. These were correlated with high-frequency ITD sensitivity to complex acoustic stimuli. These data support the notion of anatomical regions formed by specific patterns of anatomical inputs to the ICC. Such synaptic domains may represent functional zones in ICC.